1997
DOI: 10.1210/endo.138.5.5132
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental Estrogen Bisphenol A Stimulates Prolactin Release in Vitro and in Vivo*

Abstract: Environmental estrogens (xenoestrogens) are a diverse group of chemicals that mimic estrogenic actions. Bisphenol A (BPA), a monomer of plastics used in many consumer products, has estrogenic activity in vitro. The pituitary lactotroph is a well established estrogen-responsive cell. The overall objective was to examine the effects of BPA on PRL release and explore its mechanism of action. The specific aims were to: 1) compare the potency of estradiol and BPA in stimulating PRL gene expression and release in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
116
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(123 citation statements)
references
References 34 publications
5
116
2
Order By: Relevance
“…While the sensitivity of response may change with the age of the developing cultures, we have observed effects at 10 -14 M for E 2 and 10 -11 M for OP. This is in keeping with other findings that in vitro the xenoestrogens are several orders of magnitude less potent than E 2 (White et al 1994, Steinmetz et al 1997, although the sensitivity of the cultured cells appears extremely high. Significant effects of low dose E 2 and BPA have also been reported on prolactin release from cultured anterior pituitary cells obtained from adult rats of the estrogensensitive Fisher rat strain (Steinmetz et al 1997).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…While the sensitivity of response may change with the age of the developing cultures, we have observed effects at 10 -14 M for E 2 and 10 -11 M for OP. This is in keeping with other findings that in vitro the xenoestrogens are several orders of magnitude less potent than E 2 (White et al 1994, Steinmetz et al 1997, although the sensitivity of the cultured cells appears extremely high. Significant effects of low dose E 2 and BPA have also been reported on prolactin release from cultured anterior pituitary cells obtained from adult rats of the estrogensensitive Fisher rat strain (Steinmetz et al 1997).…”
Section: Discussionsupporting
confidence: 91%
“…This is in keeping with other findings that in vitro the xenoestrogens are several orders of magnitude less potent than E 2 (White et al 1994, Steinmetz et al 1997, although the sensitivity of the cultured cells appears extremely high. Significant effects of low dose E 2 and BPA have also been reported on prolactin release from cultured anterior pituitary cells obtained from adult rats of the estrogensensitive Fisher rat strain (Steinmetz et al 1997). Whilst prolactin release elicited by the lowest dose of BPA tested (10 -8 M) was not much greater than control, the response to the Table 1 Contribution of glial cells to [ 3 H]DA uptake.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…11,20) If ER participates in the regulation of BLM expression, BPA is also expected to affect BLM expression. Figure 2A shows that 10…”
Section: ϫ10mentioning
confidence: 99%
“…It has been actually shown that the in vivo effects of EDCs such as Bisphenol A mimic those of 17β-estradiol (E2), including the vaginal cornification (8), growth and differentiation of the mammary gland (9), a decreased cholesterol level in serum (10), an increased prolactin level (11), and an increased c-fos mRNA level in the uterus (8), suggesting that EDCs have enough potential to alter reproductive function and endocrine system in vivo. However, we do not know whether the EDCs can modify other cellular signaling such as growth factors or cytokines.…”
Section: Introductionmentioning
confidence: 99%